Effects of English versus heritage language on play in bilingually exposed children with autism spectrum disorder. (22nd August 2018) - Lim, Nataly; Charlop, Marjorie H.
Abstract: An alternating treatments design was used to assess the effects of the language of instruction (English vs. heritage language) on the play skills of four bilingually exposed children with autism spectrum disorder (ASD). Baseline consisted of 5‐min free‐play sessions conducted in English. Intervention consisted of two alternating conditions: 5‐min play sessions conducted in English or the participant's heritage language. During intervention, a play‐related instruction, comment, and verbal praise were made every 30 s. Results demonstrated that participants displayed more play behaviors in the heritage language than English condition. Ancillary data for one participant indicated that the occurrence of challenging behavior was lower in the heritage language condition. Results are discussed in terms of the inclusion of heritage languages in interventions for children with ASD.